The homeostatic role of neuropeptide Y in immune function and its impact on mood and behaviour. (9th January 2015) - Farzi, A.; Reichmann, F.; Holzer, P.
Abstract Neuropeptide Y (NPY), one of the most abundant peptides in the nervous system, exerts its effects via five receptor types, termed Y1, Y2, Y4, Y5 and Y6. NPY's pleiotropic functions comprise the regulation of brain activity, mood, stress coping, ingestion, digestion, metabolism, vascular and immune function. Nerve‐derived NPY directly affects immune cells while NPY also acts as a paracrine and autocrine immune mediator, because immune cells themselves are capable of producing and releasing NPY. NPY is able to induce immune activation or suppression, depending on a myriad of factors such as the Y receptors activated and cell types involved. There is an intricate relationship between psychological stress, mood disorders and the immune system. While stress represents a risk factor for the development of mood disorders, it exhibits diverse actions on the immune system as well. Conversely, inflammation is regarded as an internal stressor and is increasingly recognized to contribute to the pathogenesis of mood and metabolic disorders. Intriguingly, the cerebral NPY system has been found to protect against distinct disturbances in response to immune challenge, attenuating the sickness response and preventing the development of depression. Thus, NPY plays an important homeostatic role in balancing disturbances of physiological systems caused by peripheral immune challenge. This implication is particularly evident in the brain in which NPY counteracts the negative impact of immune challenge on mood, emotional processing and stress resilience. NPY thus acts as a unique signalling molecule in the interaction of the immune system with the brain in health and disease.